Simultaneous Determination of the Plant Growth Regulator Daminozide and its Degradation Product 1,1-Dimethylhydrazine - Chýlková, Jaromíra; Usenko, Alona; Šelešovská, Renáta; Váňa, Jiří; Sedlák, Miloš; Bartáček, Jan (BEST Servis, 2021)
The simultaneous determination of daminozide and its degradation product N,N-dimethylhydrazine via their direct electrochemical oxidation was investigated. A boron doped diamond electrode was used as the working electrode and Britton-Robinson buffer of pH 9 was applied as the suitable supporting electrolyte. The differential pulse voltammetric method for DMZ determination was developed, which provided a very low detection limit (LOD = 4.56×10-7 mol L-1). DMH could also be determined under the same experimental conditions (LOD = 2.16×10-7 mol L-1). The developed new extraction technique then allowed the determination of concentrations up to 50 times lower.
Současné stanovení růstového regulátoru rostlin daminozidu a jeho degradačního produktu 1,1-dimethylhydrazinu
Keywords: plant growth regulator; daminozide; N,N-dimethylhydrazine; voltammetry; boron doped diamond electrode; regulátor růstu rostlin; daminozid; N,N-dimethylhydrazin; voltametrie; bórem dopovaná diamantová elektroda